Kebijakan Domestik Bangladesh Terhadap Pengungsi Rohingya: Analisis Idiosinkratik atas Kepemimpinan Sheikh Hasina - Pahlawan, Harisa Firdaus; Akim, Akim; Djumala, Darmansyah (Jurnal Politik Profetik, 2025)
Bangladesh's domestic policy in responding to the Rohingya refugee crisis is influenced by Sheikh Hasina's idiosyncratic nature and her efforts to raise Bangladesh's profile in the eyes of the international community. This study uses Rosenau's idiosyncratic approach with descriptive qualitative analysis methods. Data was collected through literature review, including journals, books, internet portals, and related documents. The findings of this study indicate that idiosyncratic factors such as the personal characteristics and leadership style of Sheikh Hasina play a significant role in determining the direction and response of Bangladesh's domestic policy towards the ongoing until this study was conducted.